2021
DOI: 10.1038/s41598-021-83031-4
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency, flexibility and lead-free X-ray shielding multilayered polymer composites: layered structure design and shielding mechanism

Abstract: To overcome the severe toxicity and blind absorption zone of conventional lead-based shielding materials for X-rays in the 70–90 keV range, the lead-free multilayered polymer composites were designed and fabricated. The effects of the direction of incidence of the X-rays and number of layers as well as layer thickness ratio of the (tungsten/ethylene-octene copolymer)/(bismuth/ethylene-octene copolymer) layered composites on their shielding efficiency were studied systematically. Compared to the traditional pol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 21 publications
1
27
0
4
Order By: Relevance
“…Therefore, the less surface roughness (good dispersion of the particles in a polymer matrix) of the prepared composite corroborated well with the X-ray attenuation performance. Moreover, the D-65BTO-ER composite (highest density at 2.2 ± 0.1 g/cm 3 ) with a thickness of 2145 ± 1 μm (∼2 mm) demonstrated almost the same μ/ρ values (8.1 ± 0.3 and 6.2 ± 0.2 cm 2 /g, respectively) as the 50BTO-ER composite at both X-ray energies, which revealed that the ability of X-ray attenuation (at 80 and 100 kVp) mainly depended on (1) the dispersion of the fillers (BTO particles) in a polymer matrix (2) the density and (3) thickness of the shielding materials due to the dominant photoelectric effect at a low X-ray energy. ,, …”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Therefore, the less surface roughness (good dispersion of the particles in a polymer matrix) of the prepared composite corroborated well with the X-ray attenuation performance. Moreover, the D-65BTO-ER composite (highest density at 2.2 ± 0.1 g/cm 3 ) with a thickness of 2145 ± 1 μm (∼2 mm) demonstrated almost the same μ/ρ values (8.1 ± 0.3 and 6.2 ± 0.2 cm 2 /g, respectively) as the 50BTO-ER composite at both X-ray energies, which revealed that the ability of X-ray attenuation (at 80 and 100 kVp) mainly depended on (1) the dispersion of the fillers (BTO particles) in a polymer matrix (2) the density and (3) thickness of the shielding materials due to the dominant photoelectric effect at a low X-ray energy. ,, …”
Section: Resultsmentioning
confidence: 83%
“…Moreover, the D-65BTO-ER composite (highest density at 2.2 ± 0.1 g/cm 3 ) with a thickness of 2145 ± 1 μm (∼2 mm) demonstrated almost the same μ/ρ values (8.1 ± 0.3 and 6.2 ± 0.2 cm 2 /g, respectively) as the 50BTO-ER composite at both X-ray energies, which revealed that the ability of X-ray attenuation (at 80 and 100 kVp) mainly depended on (1) the dispersion of the fillers (BTO particles) in a polymer matrix (2) the density and (3) thickness of the shielding materials due to the dominant photoelectric effect at a low X-ray energy. 22,47,48 Further comparison between D-65BTO-ER and the 0.44 mm Pb sheet showed that the μ/ρ value of the D-65BTO-ER film was slightly lower than that of the 0.44 mm Pb sheet (9.5 and 7.3 cm 2 /g, respectively) at both energies of 80 and 100 kVp, thus indicating that the D-65BTO-ER film displayed comparable X-ray attenuation ability with the 0.44 mm Pb sheet. The mechanism related to the enhanced X-ray attenuation capacity of the prepared composites using BTO particles (BTO structure shown in Figure 1a) dispersed in the epoxy matrix can be attributed to several factors.…”
Section: Characterization Of Prepared Bto-er Compositementioning
confidence: 99%
“…To understand the shielding effect of composites against ionizing photons (X- and gamma rays), previous studies have addressed possible interactions of photons colliding with shielding materials 53 , 54 . To illustrate the shielding mechanism, one of the samples containing lead filler (PA6/PbO-20%) was selected in the present study, and its possible interactions were investigated by exhibiting the partial (including coherent, Compton, photoelectric, and pair production) and total mass attenuation coefficients in the selected energy range energies (0.001–10 MeV) 39 , and the outcomes are plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Electromagnetic radiation (X-ray) is widely applied to many nondestructive materials testing, including medical radiotherapy, medical diagnosis, and geological exploration. 1 Unfortunately, carcinogenic hazards caused by X-ray have been recognized by the International Committee on Radiological Protection, and thus the use of X-ray protective apparel is of great importance to practitioners. 2 The mechanism of Xray attenuation is mainly based on the probability of photoelectric and Compton scattering effects between the incident photons and shielding materials.…”
Section: Introductionmentioning
confidence: 99%